Identification of a Novel Gene Correlated With Vascular Smooth Muscle Cells Proliferation and Migration in Chronic Thromboembolic Pulmonary Hypertension - Wang, Feng; Sun, Congrui; Lv, Xiaoshuo; Sun, Mingsheng; Si, Chaozeng; Zhen, Yanan; Guo, Jing; Sun, Weiliang; Ye, Zhidong; Wen, Jianyan; Liu, Peng (Frontiers in Physiology, 2021)
Objective: Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by thrombofibrotic obstruction of the proximal pulmonary arteries, which result in vascular remodeling of the distal pulmonary artery. While the cellular and molecular mechanisms underlying CTEPH pathogenesis remain incompletely understood, recent evidence implicates vascular remodeling. Here, we identify the molecular mechanisms that contribute to vascular remodeling in CTEPH. Methods: Microarray data (GSE130391) for patients with CTEPH and healthy controls were downloaded from the Gene Expression Omnibus (GEO) and screened for differentially expressed genes (DEGs). DEGs were functionally annotated using Gene Ontology (GO) functional analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. A protein–protein interaction (PPI) network was constructed to identify hub genes. Finally, pulmonary artery samples were harvested from patients with CTEPH (n=10) and from controls (n=10) and primary vascular smooth muscle cells (VSMCs) were cultured. Effects of the proto-oncogene FOS on VSMC proliferation and migration were assessed using expression and knockdown studies. Results: We detected a total of 292 DEGs, including 151 upregulated and 141 downregulated genes. GO analysis revealed enrichment of DEGs in biological processes of signal transduction, response to lipopolysaccharide, signal transduction, and myeloid dendritic cell differentiation. Molecular function analysis revealed enrichment in tumor necrosis factor (TNF)-activated receptor activity, transcriptional activator activity, and protein homodimerization activity. The expression of TNF-α and its receptor (sTNFR1 and sTNFR2) were significantly higher in CTEPH group, compared with control group. KEGG pathway analysis revealed enrichment in salmonella infection, pathways in cancer, osteoclast differentiation, and cytokine-cytokine receptor interaction. Hub genes in the PPI included FOS, suggesting an important role for this gene in vascular remodeling in CTEPH. Primary VSMCs derived from patients with CTEPH showed increased FOS expression and high proliferation and migration, which was attenuated by FOS inhibition. In control VSMCs, TNF-α treatment increased proliferation and migration, which FOS inhibition likewise attenuated. Conclusion: TNF-α drives CTEPH pathogenesis by promoting VSMC proliferation and migration via increased FOS expression. These results advance our understanding of the molecular mechanisms of vascular remodeling in CTEPH, and may inform the development of new therapeutic targets.